Urgensi Penerapan Metode Long Tone Bagi Mahasiswa Mayor Instrumen Trombone Di Prodi Pendidikan Musik Universitas Negeri Padang - Ario Susanto; Erfan Erfan; Ardipal Ardipal; Agung Dwi Putra (FBS Universitas Negeri Padang, 2022)
The purpose of this study was to describe the urgency of applying the long tone method in producing sound colour for trombone major students. The research method used is descriptive qualitative. Researchers found 7 categorizations, namely: the application of the long tone method is very influential for the trombonist, the benefits of the long tone method for the trombonist, the improvement of the ability to play the Trombone for the trombonist by applying the long tone method, the effect of the application of the long tone method on the ambasir, the facilities and infrastructure needed in the application of the long tone method, the allocation of time needed during practice to apply the long tone method well, and the obstacles to implementing long tone exercises. The application of the long tone method is an important part of the formation of a quality sound colour and must be carried out consistently, regularly, and with a commitment by the trombone students of Universitas Negeri Padang.